Multi-core fiber channel equalization algorithm based on K nearest neighbor method - Yu Yahui; Tian Feng (ITM Web of Conferences, 2022)
Aiming at the channel damage problems of multi-core fiber (Multi-core Fiber, MCF), the AKNN (Adapted K-Nearest Neighbor) algorithm is proposed. The MATLAB software was used to simulate the channel of the seven-core fiber, both the inter-core crosstalk (Crosstalk, XT) and nonlinear effects were considered. Then the KNN algorithm was adapted to equalize the damaged signal at the receiver. The simulation results show that the AKNN algorithm possesses better BER performance and lower OSNR requirements with the extension of transmission distance, compared to traditional KNN algorithm.